Análisis de armónicos de focos ahorradores utilizando la transformada wavelet - Padilla Paguay, Christian Vladimir (2015)
The present thesis project develops study harmonic signals generated in compact fluorescent lamps (CFLs) origin through wavelet transform mathematical tool. Not without analyzing how they are constituted, its elements and functions. Harmonic data is presented, as they originate, what are the elements that generate, as well as what effects occur when electrical system. Also discusses some methods for the analysis of these harmonics. To perform this analysis, it is initially described consisting Wavelet theory, what their properties, types of wavelet signal decomposition using wavelet basis function Mother Haar and its relation to Fourier analysis. Analysis of harmonic signals CFLs in scale and offset based on the Gaussian function of Wavelets is also performed.